Error analysis and auto correction of hybrid solar tracking system using photo sensors and orientation algorithm. (1st September 2019) - Zhang, Junbin; Yin, Zhuojun; Jin, Peng
Abstract: In order to further improve the efficiency of daylight harvesting system, a high accuracy solar tracking system is required. The tracking error is the combined result of various sources, such as the azimuth rotational axis tilt, geo-positioning deviation, installation deviation, true north meridian deviation, calculation error and mismatch of photo sensors, etc. In this paper, we designed a dual-axis hybrid tracking system which uses GPS/BeiDou for geological location, photodiodes for closed loop tracking, and orientation algorithm for open loop tracking. The difference of our calculated the solar hour angle, altitude angle and azimuth angle to that of SOLPOS results are less than 1°. An initializing calibration is proposed to correct the errors caused by the mismatch of photodiodes. The installation deviation, geo-positioning error and true north meridian deviation for orientation algorithm are also analyzed and corrected. This field test shows that the overall tracking accuracy of the system is improved after the second dynamic compensation. The tracking system can be used in a low cost and small form factor solar tracker with easy setup by providing geological location, orientation sensing and auto corrections for weight and wind load if the photo sensors are positioned at the deflection location. Highlights: A low cost dual-axis hybrid tracking for daylight harvesting is designed and tested. It combines orientation algorithm with dynamic compensations from photo sensors. The mismatch of photodiodes is corrected in the initializing calibration. The orientation errors of dual axis are corrected by photoelectric compensations. GPS/Beiduo dual mode geo-positioning is used in orientation algorithm.